Harmonization of the Antang Kalang Muslim Community in the Practice of Ngaju Dayak Wedding Traditions - Budi Purnomo; Sanawiah; Achmadi (Universitas Islam Negeri Raden Intan Lampung, 2025)
The traditional wedding practices of the Ngaju Dayak still hold a strong position in the social life of the people of Antang Kalang District, including among the Muslim community. This condition presents normative issues related to the relationship between customary law and Islamic law, particularly in the context of the conformity of customary practices with sharia principles. Therefore, this study aims to analyze the forms of harmonization carried out by the Antang Kalang Muslim community in carrying out the traditional wedding customs of the Ngaju Dayak. This study uses a qualitative method with a sociological and legal anthropological approach. Data collection techniques include direct observation of traditional wedding practices and documentation studies of traditional documents used in their implementation. Data processing is carried out through the stages of data reduction, data presentation, and drawing conclusions, while data analysis is conducted thematically and normative-contextually. The results of the study indicate that the Muslim community of Antang Kalang has not abandoned the traditional wedding customs of the Ngaju Dayak, but rather has made adjustments through a process of selection, adaptation, and reinterpretation of traditional elements. The marriage contract is placed as the core and determinant of the validity of the marriage according to Islamic law, while the traditional wedding is carried out as a complement to social and cultural matters. This harmonization is also reflected in the use of customary marriage agreements which function as instruments of social regulation without taking over the normative authority of Islamic law.